2017
DOI: 10.5530/jppcm.2017.4.75
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone-Induced Fatal Anaphylaxis Shock at an Emergency Department: A Case Report

Abstract: Anaphylaxis in adults caused by medications such as antibiotics are quite common. To best of our knowledge, the case of anaphylaxis caused by ceftriaxone in our hospital and clinical practice is rare and especially among Saudi patients. A 31-years old Arab female patient was admitted to the emergency (ER) department due to influenza symptoms. Patient was suspected having pneumonia after examination. History indicated that she did not have penicillin allergy in the past, no history of any other concomitant medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Therefore, in the present case, cardiopulmonary arrest following anaphylaxis to ceftriaxone (Naranjo ADR probability score = 5) [12] was the probable cause of death. Published literature related to ceftriaxoneinduced anaphylaxis [13][14][15][16][17][18][19][20][21][22][23] is shown in Table 1. Moreover, a 10-year review (1998-2008) of reported cases to the Iranian Pharmacovigilance Centre showed that the most frequently reported serious events with ceftriaxone were cardiac arrest and anaphylactic and anaphylactoid reactions [24].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the present case, cardiopulmonary arrest following anaphylaxis to ceftriaxone (Naranjo ADR probability score = 5) [12] was the probable cause of death. Published literature related to ceftriaxoneinduced anaphylaxis [13][14][15][16][17][18][19][20][21][22][23] is shown in Table 1. Moreover, a 10-year review (1998-2008) of reported cases to the Iranian Pharmacovigilance Centre showed that the most frequently reported serious events with ceftriaxone were cardiac arrest and anaphylactic and anaphylactoid reactions [24].…”
Section: Discussionmentioning
confidence: 99%
“…Частота реакций гиперчувствительности, вызванных цефтриаксоном, составляет 1-3%, однако частота ана филаксии составляет всего 0,1-0,0001% [7]. При этом случаи АШ при использовании данного АБП, приведшие к летальному исходу, регулярно регистрируются во всем мире [8][9][10], в том числе среди детей [11,12]. В Китае применение цефтриаксона привело к 22 смертям по данным опубликованных с 2002 по 2009 г. клинических случаев [13].…”
Section: Introductionunclassified